Synthesis, Characterization, Biological and Photoluminescence Study of Co(II) Complexes of Fused Heterocyclic Ring Systems - Kirubavathy, Suyambulingam Jone; Chitra, Subramanian (Indian Journal of Pharmaceutical Education and Research, 2020)
Aim: To synthesize and characterize the transition metal complexes of fused heteroccylic ring systems. Background: Many of the fused ring heterocyclic compounds were found to be biologically active in the literature like anti-microbial, anti-cancer, anti-inflammatory, antioxidant and so on. The present work focus on the synthesis of the biologically active compounds. Materials and Methods: Synthesis of the ligands and the complexes are done using the standard procedures in earlier reports. Melting points were found using open glass capillaries on a Raaga melting point apparatus and are uncorrected. The percentage of C, H, N , infra-red and UV-Visible spectra of the compounds were recorded using Elementar Vario EL III CHN analyser, Shimadzu spectrophotometer (4000-400 cm-1) and Elico SL 159 UV-Vis spectrophotometer respectively. The anti-microbial activity of the compounds was carried out by well diffusion method. The anti-cancer activity of the compounds were carried out for the MCF-7 cell line (breast Cancer) using MTT assay. Discussion and Conclusion: Structural elucidation of newly synthesized Co(II) metal complexes of fused heterocyclic ring systems were done using various spectral techniques like FT-IR, 1H-NMR, Electronic and TGA-DTA studies. The anti-microbial activity of the prepared complexes and the DNA Cleavage studies were screened for various test pathogens and explained. The photoluminescence property of the fused heterocyclic ligand and their complexes were studied and compared. Fluorescence enhancement is observed in these complexes which is contradictory to the normal Fluorescence quenching phenomena by added organic derivatives, paved way for photochemical applications.
Keywords: Tetrazoloquinoxaline; Fused heterocycles; Anti-microbial; Flouresence; DNA; Cleavage; Cobalt metal complexes